PENERAPAN MEDIA CANVA DALAM PEMBELAJARAN KETERAMPILAN MENULIS TEKS PROSEDUR MENGGUNAKAN DISCOVERY LEARNING DI KELAS VII - Intan Fitri Khairunnisa; Indra Permana; Riana Dwi Lestari (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The background of this research is that students experience many factors during learning. This includes limitations in writing ability and idea development. During learning, the teacher usually only learns through monotonous methods without media and then only gives assignments. The method that is often used is the lecture method from textbooks, which does not require students to be active. The formulation of the research problem is as follows. 1) How does Canva media affect the ability to write procedural text? 2) How is the implementation of learning with discovery learning models in students' writing abilities? The research objective was to determine the effect of Canva media on the ability to write Indonesian procedural texts and the effect of implementing the discovery learning model on writing ability. The discovery learning model aims to facilitate the development of ideas in writing. One of the efforts to improve procedural text writing skills is to conduct research using discovery learning assisted by Canva media. Canva is an online application designed for more interactive and creative learning in writing. The method used is descriptive qualitative using observation techniques, data collection and tests. The subjects in this study were 30 students in class VII-E of SMPN 3 Cimahi. The results showed that the discovery learning model can be used effectively in learning procedural text writing skills. Judging from the results of students' ability to write procedural texts, they generally get good criteria because they get scores above 80.